Implementation of Project-Based e-LKPD on Banana Peel Waste Processing to Enhance Students’ Creative Thinking Skills - Dwi - Pratiwi; Kartini Herlina; Ryna Aulia Falamy; Abdurrahman Abdurrahman (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
The lack of creative thinking skills of students in learning alternative electrical energy highlights the need for more contextual and project-oriented learning activities. This study investigated the effectiveness of project-based electronic worksheets on banana peel waste processing implemented through the PjBL-STEM learning model in improving students’ creative thinking skills. A quasi-experimental design supported by qualitative interview data was employed in this research to obtain a deeper understanding of students’ learning experiences. The participants consisted of two classes from a state senior high school in Lampung, Sumatra. Data were collected using essay-based test instruments developed to assess the indicators of fluency, flexibility, originality, and elaboration. The quantitative findings showed that students’ creative thinking skills improved significantly after the implementation of the project-based e-LKPD, as indicated by high N-gain scores of 0.72 and 0.75, along with significant paired sample t-test results (sig. < 0.05). Furthermore, no statistically significant difference was found based on gender (sig. > 0.05), although several indicators demonstrated descriptive variations. Overall, the implementation of project-based e-LKPD through the PjBL-STEM learning model contributed positively to the development of students’ creative thinking skills and may serve as an innovative alternative in physics learning.